Nikah di bawah tangan perspektif yuridis dan sosiologis - Subarman, Munir (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
The purpose of this paper is to determine the implementation of unregistered marriages and its obstacles in social life. The author uses a qualitative approach with descriptive methode which describes systematically, factual, and accurate information on the facts, properties and relationships among actualized phenomena. Siri marriage is a marriage conducted in accordance with terms and pillars of marriage in Islam, but not with the Registrar of Marriage Officer (VAT). Unregistered marriages is considered legitimate according to religion. Eventhough it causes problems because it is not listed in state law. So it will have difficulty regarding divorce and division of matrimonial property, as well as an impact on the status of children, guardianship status of marriage rights, and inheritance rights.